I politici e l’immigrazione su Facebook: come si (de)legittima il discorso migratorio durante l’emergenza sanitaria - Lucchesi, Dario; Romania, Vincenzo (SocietàMutamentoPolitica, 2023)
In this article we analyse how the immigration issue is narrated during the Covid-19 outbreak by several Italian political actors. We select Facebook as the main digital arena of political communication in the Italian public sphere. Quantitative analysis and Critical Discourse Analysis have been applied to politicians’ posts aiming at identifying the linguistic strategies that contribute to instrumentalizing the emergency and aim to reinforce the politicization of the issue. Findings suggest that the main discursive strategies used by politicians do not only include migrants as a danger for the spread of the virus, but the migratory narration is systematically organized on negative campaigning blaming political opponents. The contribution helps to reveal how the anti-migration discourse is reproduced during the Covid-19 outbreak and how the politicization of the migration serves as a context for the normalization of migrant’s exclusion.